Demographic Characteristics, Perfectionism, and Productivity Among Certified Public Accountants - Guillermo, Haries Ben B. (Randwick International of Education and Linguistics Science Journal, 2025)
This study examined perfectionism as a predictor of productivity among Certified Public Accountants (CPAs) in Cavite. A total of 102 licensed CPAs participated, representing diverse demographics in terms of age, sex, civil status, educational attainment, years of experience, employment sector, and organizational position. Using a researcher-made survey questionnaire, data were analyzed through descriptive statistics, correlation, and multiple regression. Findings revealed that participants exhibited a high level of adaptive perfectionism (M = 4.540, SD = 0.507) and a neutral level of maladaptive perfectionism (M = 3.072, SD = 0.835). Productivity across five dimensions—task completion efficiency, accuracy in financial reporting, workload management, meeting deadlines, and adaptability to work demands—was consistently high. Correlation analysis showed that age, educational background, and years of experience were significantly related to productivity, while sex, civil status, type of employment, and position were not. Adaptive perfectionism was positively and significantly correlated with productivity (ρ = .427, p < .001) and emerged as the only significant predictor in regression analysis (B = 0.234, β = .281, p = .015). Maladaptive perfectionism demonstrated no significant relationship. These findings validate the Achievement Goal Theory and Cognitive Appraisal Theory, affirming that adaptive perfectionism—when characterized by high personal standards, motivation, and resilience—serves as a critical driver of productivity in the accounting profession.